2007
DOI: 10.1080/17453670710013645
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of peri- and intraarticular analgesia with femoral nerve block after total knee arthroplasty: A randomized clinical trial

Abstract: BackgroundPostoperative pain after total knee arthroplasty (TKA) can be difficult to manage and may delay recovery. Recent studies have suggested that periarticular infiltration with local anesthetics may improve outcome.Methods 80 patients undergoing TKA under spinal anesthesia were randomized to receive continuous femoral nerve block (group F) or peri-and intraarticular infiltration and injection (group I). Group I received a solution of 300 mg ropivacaine, 30 mg ketorolac, and 0.5 mg epinephrine by infiltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
283
4
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(315 citation statements)
references
References 13 publications
20
283
4
8
Order By: Relevance
“…It is also conceivable that much of the difference seen may be attributed to the FNB, which is expected to be effective during the first 24 postoperative hours. This contrasts with the findings of Toftdahl et al [18] who found analgesic benefits of local ropivacaine over a continuous FNB but can perhaps be explained by the fact that the injection was administered periarticularly in that study. This then raises the question of whether the location of the local anesthetic plays a role in its efficacy.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…It is also conceivable that much of the difference seen may be attributed to the FNB, which is expected to be effective during the first 24 postoperative hours. This contrasts with the findings of Toftdahl et al [18] who found analgesic benefits of local ropivacaine over a continuous FNB but can perhaps be explained by the fact that the injection was administered periarticularly in that study. This then raises the question of whether the location of the local anesthetic plays a role in its efficacy.…”
Section: Discussioncontrasting
confidence: 99%
“…In fact, we found improved pain scores during the first 24 postoperative hours with an epidural plus FNB. However, the effect size was not large, and its clinical significance may be only borderline; in fact, even the average maximum pain scores in the ropivacaine group were low and were comparable to prior studies that have supported intraarticular ropivacaine as an analgesic option after TKA [8,18]. It is also conceivable that much of the difference seen may be attributed to the FNB, which is expected to be effective during the first 24 postoperative hours.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In a previous randomized controlled trial (RCT) evaluating PAI, we showed that mean morphine consumption was lower in the PAI group than the control group up to 40 hours postoperatively (46.7 mg compared with 68.6 mg, respectively) [27]. Other authors compared different PAI protocols versus femoral nerve block and have reported lower pain scores and consumption of opioids in their PAI group [21,26]. Carli et al [8] compared the analgesic effect of PAI versus femoral nerve block plus PAI into the posterior knee capsule and found that the femoral nerve block plus posterior PAI was associated with lower opioid consumption and better recovery at 6 weeks as measured by functional walking capacity (2-and 6-minute walk tests) than PAI alone.…”
Section: Introductionmentioning
confidence: 96%